Faktor Yang Mempengaruhi Masyarakat Menggunakan Aplikasi Lapor Polisi Kita di Kabupaten Sleman - Claritza Destya Anggraeny; Ulung Pribadi; Muhammad Iqbal (Universitas Muhammadiyah Ponorogo, 2021)
The Republic of Indonesia Special Region of Yogyakarta Police (Polda DIY) launched a Polisi Kita Application program as a means to provide services to the community based on real-time online. The purpose of this study is to analyze the factors that influence the application of e-government to the use of the Polisi Kita Application program in the Yogyakarta Regional Police in 2018. The theory used to analyze this phenomenon is the Unified Theory of Acceptance and Use of Technology (UTAUT) theory. This research uses quantitative research methods. The number of research respondents was 99 respondents who were taken using Accidental Sampling techniques and processed using SmartPLS 3.0 Software. The results of this study state that the discovery of factors that influence online-based public services using UTAUT theory is proven to have a significant influence on the use of public services. Based on the results of the analysis in finding the strength of the relationship between variables X and Y found the highest correlation coefficient results in the Behavioral Intention variable with the Ut variable. E-service (Our Police Report) is (0.920). The Police Application We get a good response from the public regarding the ease of using the Police Application. To be able to maintain and improve performance, the Yogyakarta Regional Police should add a feature to verify the user's cellphone number via SMS or email so that the level of security of the user's report is better.